Evaluating the SWS bolted connection strength of Bitis wood - Erwan, Sukarman; Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don; Abdul Azim, Abdullah; Siti Hanim, Sahari; Nur Liza, Rahim; Pierre, Quenneville (MIM RESEARCH GROUP, 2023)
The current study was conducted to evaluate the strength of the steel-wood-steel (SWS) bolted connections of Bitis wood. The wood was chosen because it is commonly used as the structural elements of the as-built floor and roof diaphragms in Malaysian unreinforced masonry (URM) buildings. This present work was performed to continue the initiation of the wood database development for the purpose of retrofitting the wall-diaphragm connections of the URM building. The bolted connection testing was the main experimental investigation, where a total of eighteen groups of different connection configurations were tested, each consisting of ten specimens. The embedding strength tests, moisture content and density tests were also conducted to determine the wood's basic properties. The results obtained from this experimental study were utilized for verifying the prediction effectiveness of the existing design equations, namely the Malaysian Timber Standard (MS544-5), the European Yield Model (EYM), and the Row Shear Model (RSM). From the comparison made between the prediction values and the experimental results, the MS544-5 was found to be too conservative, whereas a combination of the EYM and RSM is recommended for predicting the bolted connection strength of the Bitis wood.